La villa de Tordesillas y sus relaciones regionales - Bahr, Cecilia (Estudios de Historia de España, 2017)
Tordesillas, profusely named in the Castilian documents due to its convent of Santa Clara or its location as place of transit or residence for the Court, is an interesting element for the examination of Medieval Spanish History. Anyway, from the study of its space and internal organization, the conclusion is that its case cannot be analyzed if the surrounding region, with which the city maintained institutional, economic and poblational contacts, is not included.